Analyzing cognitive and spelling skills in Spanish-speaking English-language learners and English-speaking Canadian learners (European Journal of Education and Psychology, 2010)
The principal purpose of this study has been to analyze the cognitive processes and spelling skills in Spanish-speaking English-language learners. A sample of English-speaking Canadian learners and Spanish-speaking English-language learners was selected from different Canadian schools in the Vancouver District within British Columbia's province. We examined cognitive and spelling skills of English-speaking students and Spanish-speaking English language learners in the primary grades. We hypothesized that there would be a positive transfer from cognitive and linguistic processes from L1 to L2 spelling skills development, if no significant differences were observed among native English speakers and Spanish-language learners on these measures. There were no significant differences between the English –language learners and the native English speakers on measures of phonological awareness and spelling skills. However, English-speaking Canadian learners performed better than Spanish-speaking English-language learners on vocabulary and syntactic awareness.